Interventional Radiology Procedures after Pancreatic Resections for Pancreatic and Periampullary Diseases - Casadei, Riccardo; Ricci, Claudio; Giampalma, Emanuela; D’Ambra, Marielda; Taffurelli, Giovanni; Mosconi, Cristina; Golfieri, Rita; Minni, Francesco (JOP. Journal of the Pancreas, 2014)
Context The use of interventional radiology has increased as the first-line management of complications after pancreatic resections. Methods Patients in whom interventional radiology was performed were compared with those in whom interventional radiology was not performed as regards type of pancreatic resection, diagnosis, postoperative mortality and morbidity, postoperative pancreatic fistula postpancreatectomy haemorrhage, bile leakage, reoperation rate and length of hospital stay. Our aim was to evaluate the usefulness of interventional radiology in the treatment of complications after pancreatic resection. Results One hundred and eighty-two (62.8%) out of 290 patients experienced postoperative complications. Interventional radiology procedures were performed in 37 cases (20.3%): percutaneous drainage in 28, transhepatic biliary drainage in 8 and arterial embolisation in 3 cases. Technical success was obtained in all cases and clinical success in 75.7%. Reoperation was avoided in 86.5%. In patients with major complications, clinically relevant postoperative pancreatic fistula and bile leaks as well as those with late postpancreatectomy haemorrhage (P=0.030) and patients with postpancreatectomy haemorrhage grade C (P=0.029), interventional radiology was used (P<0.001, P<0.001 and P=0.009, respectively) significantly more frequently than in the remaining patients. The reoperation and mortality rates were similar in the two groups (P=0.885 and P=0.100, respectively) while patients treated with interventional radiology procedures had a significant longer length of hospital stay than those in the non-interventional radiology group (37.5 ± 23.4 vs. 18.7 ± 11.7 days; P<0.001). Conclusions Interventional radiology procedures were useful, especially for patients with postoperative pancreatic fistulas and bile leaks in whom reoperation was very often avoided. Image: Surgeons from the patient's wiev